Analysis of the Effect of Gross Regional Domestic Product, Unemployment and Human Development Index on Poverty in East Java, Indonesia - Dicky Anggoro; Arimurti Kriswibowo (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this study is to analyze the effect of regional gross domestic product, unemployment and the human development index on Poverty in East Java Province in 2010-2021. The purpose of this research is to find out whether the independent variables affect the dependent variable. This study uses multiple linear regression methods. The population in this study is from 2010-2021. Then the population in this study amounted to 11 populations. And the sample of this study took from each variable, namely GRDP, Unemployment, HDI and poverty, with a total of 11 samples. This research produces exciting findings, including the gross regional domestic product variable that does not affect poverty, then the unemployment variable that affects povert, and the variable human development index affects poverty.